The Influence Of Social Media Marketing On Purchasing Decisions At Triloka Company - Nur Fadilah; Nadya Aurelle Dwisyah; Zulkaida Akher (International Conference On Digital Advanced Tourism Management And Technology, 2023)
The purpose of this study is to determine how the usage of social media affects elite home purchase choices at PT. Triloka Kendari in Kendari Regency. This study focuses on elite house purchasers who work with PT. Kendari Triloka in Kendari Regency. The accidental sampling approach was used to choose this study's 81 respondents. This study collects primary data via the distribution of questionnaires. This study employs multiple linear regression analysis with t-test hypothesis testing. The test findings indicate that service quality and social media marketing factors impact the choice to buy exclusive home at PT. Triloka Kendari. The independent variable has an 18.5% effect on the dependent variable, whereas factors not addressed in this research affect 26.54% of the total.